2017
DOI: 10.1021/acsomega.7b01546
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Dye Aggregate Assembly Enables Ratiometric Detection and Discrimination of Lysine and Arginine in Aqueous Solution

Abstract: Constructing sensor systems for rapid and selective detection of small biomolecules such as amino acids is a major area of focus in bioanalytical chemistry. Considering the biological relevance of arginine and lysine, significant efforts have been directed to develop fluorescent sensors for their detection. However, these developed sensors suffer from certain disadvantages such as poor aqueous solubility, technically demanding and time-consuming synthetic protocols, and more importantly, most of them operate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…9). This proposition was well supported by absorbance, fluorescence CD spectroscopy and emission life time studies (Pettiwala and Singh, 2017).…”
Section: Thioflavin-t Interaction With Supramolecularmentioning
confidence: 59%
See 4 more Smart Citations
“…9). This proposition was well supported by absorbance, fluorescence CD spectroscopy and emission life time studies (Pettiwala and Singh, 2017).…”
Section: Thioflavin-t Interaction With Supramolecularmentioning
confidence: 59%
“…This red-shift in absorption spectra indicated the dissociation of ThT aggregates from SCD surface, and release of ThT monomer in bulk water. The excited-state lifetime results were in conjunction with fluorescence and absorbance studies wherein it was observed that addition of arginine in ThT-SCD results in faster excited-state lifetime, thus indicating the disruption of ThT-SCD complex and release of ThT monomer in solution (Pettiwala and Singh, 2017).…”
Section: Thioflavin-t Interaction With Supramolecularmentioning
confidence: 83%
See 3 more Smart Citations